Efeito inibitório do Ebselen, do disseleneto de difenila e do ditelureto de difenila sobre a atividade da LDH de mamíferos - Lugokenski, Thiago Henrique (2009)
Ebselen is a seleno compound whose antioxidant properties have been attributed to its thiol-peroxidase and thioredoxin-like activity: it decomposes peroxides at the expense of reduced thiols. However, the excessive oxidation of thiols can be potentially toxic when it is not associated with peroxides degradation. Thus, this work investigated if LDH can be a possible in vitro target to toxicity of ebselen in comparison with diphenyl diselenide and diphenyl ditelluride, two antioxidant organochalcogens that can easily interact with thiol in exchange reaction. LDH inhibition was tested in homogenates from rat liver and heart, and in purified LDH from rabbit muscle. Ebselen was the most potent inhibitor of LDH. A maximal inhibitory effect was obtained at 2 μM to LDH purified and at 20 μM to LDH from heart and liver homogenates. Moreover, diphenyl diselenide followed by diphenyl ditelluride also presented a significant inhibitory effect on LDH activity. In addition, we observe that DTT was able to revert the inhibition of LDH induced by all compounds tested, confirming the involvement of essential thiol groups on LDH inhibition by organocalchogens. In conclusion, our results show that liver and heart LDH may be a possible target for toxicity of organochalcogens at relative low concentrations. However, the protection afforded by substrates may hide this potential molecular target of organochalcogenides. Our results also indicate that the use of LDH as a marker of cell viability may be biased by a direct inhibitory effect of ebselen or other chalcogenides on LDH, resulting in false protection in in vitro system.